HUBUNGAN KEPEMIMPINAN DAN MOTIVASI KERJA DENGAN KEPUASAN KERJA (Studi pada Direktorat Jenderal Bina Pembangunan Daerah Departemen Dalam Negeri) - Sorni Paskah Daeli (Widyariset, 2010)
The aim of this study is to analyze the correlation between the leadership, motivation, and job satisfaction. The focus of analysis is to clarity the perspective that high score of leadership and motivation to be a job satisfaction. This research used scale instrument of leadership, motivation, and job satisfaction to collect the data. This research was done towards 389 staffs of Directorate General of Regional Development-Ministry of Home Affair. In analyzing the data, the researcher used product moment correlation that is provided by SPSS 10.0. The result showed thatthere is a positive correlation between leadership, motivation, and job satisfaction at office.